Analisis Kemampuan Pemecahan Masalah Menurut Polya Dalam Pembelajaran Problem Based Learning Berdasarkan Gaya Berpikir Gregorc Siswa Kelas Vii Smp Negeri 1 Gondang Tahun Ajaran 2016/2017 - Kurniawati, Wibrika; , Dr. Sumardi, M.Si (2017)
This study aims to describe the problem solving skill of students in terms of thinking style with a category quential concrete, sequential abstract, random concrete and random abstract with the model of problem based learning. This type of research is qualitative. The subject of research are one students for each style. The technique of data collection of research are questionnaire, test and interviews. The data analyze of research are data reduction, data presentation and get conclusion and verification. The results showed that: (1) Students of sequential concrete, understand the problem by writing what is know and ask as well as speak it by following the information in question without analyzing, only able to make one settlement plan, able to write a complete processing step and rechecking the answers. (2) Students of sequential abstract, understand the problem doesn't write what is known and asked as well as speak it by analyzing using his own words, able to make more than one settlement plan, able to write a complete processing step and rechecking the answers. (3) Students of random concrete, understand the problem by writing what is know and ask as well as speak it by following the information in question without analyzing, only able to make one settlement plan, inclined to be less complete to write processing step and doesn't check back after completion of work. (4) Students of random abstract, understand the problem doesn't write what is known and asked as well as speak it by analyzing using his own words, able to make more than one settlement plan, able to write a complete processing step and rechecking the answers.